Orientation and Mobility During COVID-19 and the Effect on Psychosocial Functioning. (November 2022) - Kaiser, Justin T.; Fast, Danene; DeGrant, Jasamyn N.; Welch-Grenier, Stephanie
Introduction: This research explored the psychosocial effects observed during the COVID-19 pandemic as it relates to orientation and mobility (O&M) services for children with visual impairments. The survey asked professionals to identify what were their experiences in providing O&M instruction in-person and online and to describe their interactions with students and families during the fall of 2020.Methods: The online survey results included open-ended responses from 166 O&M specialists. The authors used thematic analysis to examine and code participants' qualitative responses.Results: Psychological and social effects were identified as a major theme across the participants for how they affected an individual's health, well-being, and ability to complete aspects of O&M lessons. Professionals were challenged with providing appropriate instruction given the risks associated with COVID. Additionally, children with visual impairments became more isolated and less physically active over time.Discussion: Professionals, students, and parents often placed their concerns aside with the idea that changes to O&M services were a temporary measure with the student's best interest in mind. As the pandemic became prolonged, the effects on individuals became more pronounced.Implications for Practitioners: These circumstances raise many questions about the effectiveness of virtual instruction in O&M and its effect on professionals, students, and families. The importance of O&M becomes much more evident when considering the isolation many students experienced as a result of quarantine events.